1987
DOI: 10.1056/nejm198703053161005
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Adenosine Deaminase Deficiency with Polyethylene Glycol–Modified Adenosine Deaminase

Abstract: We treated two children who had adenosine deaminase deficiency and severe combined immunodeficiency disease by injecting bovine adenosine deaminase modified by conjugation with polyethylene glycol. The modified enzyme was rapidly absorbed after intramuscular injection and had a half-life in plasma of 48 to 72 hours. Weekly doses of approximately 15 U per kilogram of body weight maintained plasma adenosine deaminase activity at two to three times the level of erythrocyte adenosine deaminase activity in normal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
188
0

Year Published

1990
1990
2005
2005

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 437 publications
(189 citation statements)
references
References 38 publications
0
188
0
Order By: Relevance
“…Whereas PEG-ADA was detectable in the blood of this animal, it was not detected in any of the tissues examined, including the thymus, spleen, liver, kidney, and lung. These data suggested that most if not all of the PEG-ADA in ADAdeficient mice was found in the circulatory system, as has been assumed to be the case in humans (2,28).…”
Section: Stability and Distribution Of Peg-ada Inmentioning
confidence: 78%
See 2 more Smart Citations
“…Whereas PEG-ADA was detectable in the blood of this animal, it was not detected in any of the tissues examined, including the thymus, spleen, liver, kidney, and lung. These data suggested that most if not all of the PEG-ADA in ADAdeficient mice was found in the circulatory system, as has been assumed to be the case in humans (2,28).…”
Section: Stability and Distribution Of Peg-ada Inmentioning
confidence: 78%
“…For determination of ADA trough values, heparinized blood samples were collected from the tail vein of mice just prior to the next injection of PEG-ADA, and plasma isolated by low-speed centrifugation. ADA specific activity in plasma was determined using established protocols (28).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternative options are haploidentical BMT 3,4 and enzyme replacement with polyethylene glycol-conjugated bovine ADA (PEG-ADA). 5 In the mid 1980s gene transfer was proposed as a therapy for ADA deficiency. The simple regulation of the ADA gene 6 and the expected selective advantage of gene-corrected cells suggested ADA deficiency as an ideal initial candidate disease to test gene therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Polyethylene glycol-conjugated bovine ADA (PEG-ADA) is a replacement therapy for ADA deficiency. 3,4 PEG prolongs the half-life of the ADA enzyme by reducing its catabolism. By greatly reducing the levels of toxic metabolites, PEG-ADA therapy has been successful in preventing infections, although restoration of immune function is only partial.…”
mentioning
confidence: 99%